2024
DOI: 10.1002/mrm.30001
|View full text |Cite
|
Sign up to set email alerts
|

Universal dynamic fitting of magnetic resonance spectroscopy

William T. Clarke,
Clémence Ligneul,
Michiel Cottaar
et al.

Abstract: PurposeDynamic (2D) MRS is a collection of techniques where acquisitions of spectra are repeated under varying experimental or physiological conditions. Dynamic MRS comprises a rich set of contrasts, including diffusion‐weighted, relaxation‐weighted, functional, edited, or hyperpolarized spectroscopy, leading to quantitative insights into multiple physiological or microstructural processes. Conventional approaches to dynamic MRS analysis ignore the shared information between spectra, and instead proceed by ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Finally, future work should also explore whether model-based FPC can be directly incorporated into more dynamic and complex 2D modeling scenarios like diffusion-weighted, functional, edited, hyperpolarized MRS, and relaxometry 45 . Recent studies of 2D modeling 21,45 have generally found improvements in fitting uncertainty and precision of target parameter estimation in several dynamic data scenarios. Certain benefits of 2D-LCM in uncertainty estimation were also shown for conventional 1D-MRS data 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, future work should also explore whether model-based FPC can be directly incorporated into more dynamic and complex 2D modeling scenarios like diffusion-weighted, functional, edited, hyperpolarized MRS, and relaxometry 45 . Recent studies of 2D modeling 21,45 have generally found improvements in fitting uncertainty and precision of target parameter estimation in several dynamic data scenarios. Certain benefits of 2D-LCM in uncertainty estimation were also shown for conventional 1D-MRS data 22 .…”
Section: Discussionmentioning
confidence: 99%
“…2D modeling can be biased by the incorrect selection of spectral models that do not describe data behavior correctly 21 -either in the spectral dimension or the second, indirect dimension 45 . It is wellknown that the choice of spectral model, modeling parameters, starting values, upper/lower bounds, regularizations, and penalties has an outsized impact on modeling results, even for 1D-LCM 30,[46][47][48][49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…Alternative MRS analysis approaches involve 2D fitting, whereby multiple spectra are fit to a metabolite basis simultaneously - reducing the number of parameters requiring optimisation resulting in more accurate estimates. Whilst the advantages of 2D fitting in MRS have been long established in various contexts (Chong et al, 2011; Schulte & Boesiger, 2006; Van Ormondt et al, 1990) there has been renewed interest in the application of 2D fitting to functional and diffusion MRS (Clarke et al, 2024; Tal, 2023). Other approaches involve combining conventional 1D fitting with a GLM applied to the metabolite time-courses (Ligneul et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Cramér–Rao lower bounds for Glu and GABA fitting were not significantly different across all scans. Recent dynamic fitting approaches for MRS, incorporating temporal modelling of the stimulation periods, may offer improved ability to detect changes compared with block-averaging (Clarke et al, 2024; Tal, 2023).…”
Section: Discussionmentioning
confidence: 99%